2020
DOI: 10.1111/tbed.13948
|View full text |Cite
|
Sign up to set email alerts
|

The hard numbers of tuberculosis epidemiology in wildlife: A meta‐regression and systematic review

Abstract: Tuberculosis (TB) is a widespread disease that crosses the human and animal health boundaries, with infection being reported in many wild species, from temperate and subtropical to arctic regions. Often, TB in wild species is closely associated with disease occurrence in livestock but the TB burden in wildlife remains poorly quantified on a global level. Through a meta-regression and systematic review, this study aimed to summarise global information on the prevalence of TB in commonly infected wildlife specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 79 publications
3
18
0
1
Order By: Relevance
“…TB prevalence varied strongly between the years, with over one quarter of the population displaying clinical signs in some years. TB prevalence reported in this study is comparable with those reported from other well‐studied species [∼12% for European badgers ( Meles meles ) to ∼32% for red deer ( Cervus elaphus ) and wild boar ( Sus scrofa ); see Reis et al., 2021], both with regard to overall (16.2%) and annual prevalence. Previous studies using diagnostic tools on subset of the study population to detect TB reported prevalence between 24% (Drewe, 2010) and up to 82.4% of individuals of exposed groups (Clarke et al., 2016), implying that by using clinical signs, the true extent of Mycobacterium infection prevalence is underestimated.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…TB prevalence varied strongly between the years, with over one quarter of the population displaying clinical signs in some years. TB prevalence reported in this study is comparable with those reported from other well‐studied species [∼12% for European badgers ( Meles meles ) to ∼32% for red deer ( Cervus elaphus ) and wild boar ( Sus scrofa ); see Reis et al., 2021], both with regard to overall (16.2%) and annual prevalence. Previous studies using diagnostic tools on subset of the study population to detect TB reported prevalence between 24% (Drewe, 2010) and up to 82.4% of individuals of exposed groups (Clarke et al., 2016), implying that by using clinical signs, the true extent of Mycobacterium infection prevalence is underestimated.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, a well‐founded understanding of transmission and host–pathogen dynamics is imperative for the development of adequate TB surveillance and management strategies (de Lisle et al., 2002). However, despite intense research efforts in several TB host systems (reviewed in Reis et al., 2021), quantitative data on TB exposure, prevalence and progression are still rare for many wildlife species affected by TB.…”
Section: Introductionmentioning
confidence: 99%
“…It causes animal TB primarily in cattle, but also in other livestock species [3]. Some wildlife species are pathogen reservoirs and infection amplifiers, helping to sustain TB across a variety of ecosystems in different geographic locations [4]. Well-known epidemiological scenarios referred to in the literature include the Iberian Peninsula, United Kingdom, Australia, New Zealand, South Africa and USA [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In short, there are many flaws in the field of preventing zoonotic exposure to TB in this specific risk population, the large game hunters [ 18 ]. Bad practices in handling hunted carcasses potentially infected with TB increase the risk of occupational exposure.…”
Section: Discussionmentioning
confidence: 99%